KUASA SIMBOLIK PATUNG RUANG PUBLIK : STUDI KASUS DI WILAYAH KOTA SURAKARTA - Himawan, Muhammad Hendra (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2018)
ABSTRACTThis article is the result of research examining how the development of public art, definitive public space sculpture and conventions that surround it, to see the extent to which the political dimension sees how to make the existence of public sculpture as a tool of legitimacy of power, development of image and power and contact with social discourse that develops in society.From the qualitative method of the Slamet Riyadi Statue on Jalan Slamet Riyadi, the Major Achmadi Statue in the Banjarsari Lima Proximity (Proliman), 45 Banjarsari Monument Statue (Serangan 4 Hari Monument in Surakarta) is located in Banjarsari Park, and the Statue Soekarno at Manahan Sports Complex, Surakarta, found that the existence of the statue was a proof of how the symbolic system was carried out to legitimize power by government authorities.Various forms of work that illustrate the dominance of militaristic icons compared to civilian icons, which shows how the quo vadis of military-civil relations are explicit and implied. Furthermore, this research found evidence that so far there have been a lot of public space sculptural works that do not idolize the public's need for living space.Symbolic power practices are continuously echoed through a system of visual language and symbolization that shows how power sneaks under the conscious space of society. The community is not aware of how the power system stands and hides behind these sculptures of public space, whatever the reason for their establishment; inheritance of nationalism, development of moral values, even ideology.Keywords: history, public space sculpture, symbolic of power, Surakarta City